Lesion-Constrained Electrical Source Imaging: A Novel Approach in Epilepsy Surgery for Tuberous Sclerosis Complex. Issue 1 (January 2020) - Peters, Jurriaan M.; Hyde, Damon E.; Chu, Catherine J.; Boom, Merel; Scherrer, Benoit; Madsen, Joseph R.; Stone, Scellig S.; Ouaalam, Hakim; Prabhu, Sanjay P.; Sahin, Mustafa; Warfield, Simon K.
Abstract : Purpose: Electrical source imaging may yield ambiguous results in multilesional epilepsy. The aim of this study was to test the clinical utility of lesion-constrained electrical source imaging in epilepsy surgery in children with tuberous sclerosis complex. Methods: Lesion-constrained electrical source imaging is a novel method based on a proposed head model in which the source solution is constrained to lesions. Using a goodness of fit analysis, we rank-ordered individual tubers by their ability to approximate interictal and ictal EEG data. The overlap with the surgical resection cavity was determined qualitatively, and placed findings in the context of epilepsy surgical outcome, and compared with the low-resolution brain electromagnetic tomography solution. Results: Low-resolution brain electromagnetic tomography predicted the surgical cavity in only one patient with good outcome (true positive) and localized to outside of the cavity in two patients with a good outcome (false negative). In one patient with a poor outcome, the interictal low-resolution brain electromagnetic tomography solution overlapped with the cavity (false positive). Lesion-constrained electrical source imaging of ictal EEG data identified tubers concordant with the resection zone in three patients with a good surgical outcome (true positive) and appropriately discordant in three other patients with a poor outcome (true negative). Conclusions: Lesion-constrained electrical source imaging on low-resolution EEG data provides complementary information in the presurgical workup for patients with tuberous sclerosis complex, although further validation is required. In the appropriate clinical context, the yield of source localization on low-resolution EEG data may be increased by reduction of the solution space.